SMART SEWERAGE WITH WEB MONITORING SYSTEM - PHRECHLLA SULAN, PETER (Universiti Malaysia Sarawak (UNIMAS), 2023)
I have proposed an smart sewerage system that will be monitored through web and keep the data in the cloud. This project will be develop using Arduino Uno and NodeMCU ESP32 that connected with few sensors that help to capture data and sending the data to cloud for analysis. Sensors that include in this project is MQ2 Gas Sensor. This sensor is for detecting hazardous gases depending on changes of resistance. Next is DS18B20 Temperature Sensor for measuring the temperature of water. Lastly is Ultrasonic Sensor that produce the ultrasonic sound wave for measuring the distance of target. Additionally, this project also focusing on developing system for reviewing the data that has been captured by sensors. The data will be keep safely inside cloud for generating the report for analysis.